2021
DOI: 10.1177/08943184211010462
|View full text |Cite
|
Sign up to set email alerts
|

Impostor Phenomenon: A Concept Analysis

Abstract: Impostor phenomenon was first described by Clance and Imes in 1978 as the disbelief of own person’s capacities and skills in overachieving women. Since then, studies have focused on causes and characteristics of such self-perception. This negative thought impedes professionals to achieve full potential of their abilities, triggering a series of unpleasant reactions like anxiety or poor patient outcome. This concept analysis aims to provide better understanding of the impostor phenomenon and its impact on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Second, we found that the nursing field has given little attention to the IP. Research on the IP focuses primarily on the universality of IP in the population, and thus, little is known about the impact of different activities to overcome the experience of self-doubt and its consequences, a finding that aligns with the study results of Gómez-Morales (2021) .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Second, we found that the nursing field has given little attention to the IP. Research on the IP focuses primarily on the universality of IP in the population, and thus, little is known about the impact of different activities to overcome the experience of self-doubt and its consequences, a finding that aligns with the study results of Gómez-Morales (2021) .…”
Section: Discussionmentioning
confidence: 85%
“…The impostor phenomenon (IP), which is a concept that was proposed by Clance and Imes (1978) , refers to “a false internal experience of low intelligence or ability.” A literature review indicates that many studies have shown that the IP exists in different populations, such as managers, resident physicians, and medical students ( Rohrmann et al, 2016 ; Villwock et al, 2016 ; Gottlieb et al, 2020 ), but that it is also common among nursing students and nurses ( Christensen et al, 2016 ; Gill, 2020 ). While the IP has been well described in other fields, research on IP in the nursing field is limited, with available studies focusing primarily on the universality of the IP ( Gómez-Morales, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a strong preceptor increases the retention of novice nurses and helps decrease the effects of imposter syndrome. 1,7,9 Characteristics of a good preceptor include a willingness to educate, evaluate, and socialize novice nurses. 10 Nurse leaders should recognize that qualified preceptors are difficult to divert from essential clinical practice units during the pandemic or other emergencies.…”
Section: Supporting New Nursesmentioning
confidence: 99%
“…New nurses experiencing imposter syndrome are more likely to conceal what they perceive to be their ineptitude and unworthiness. Nurses that have experienced imposter syndrome have described this feeling as paralyzing and stressful with an inability to feel competent in their care 9. This syndrome may be more prevalent than ever due to today's healthcare environment.…”
Section: Imposter Syndromementioning
confidence: 99%